Slope stability assessment for block-in-matrix composite-materials by the tortuous surface method (2019)
This thesis deals with the general problem of slope stability analysis in bimsoils/bimrocks and tortuous failure surfaces in slopes. The problem was handled by means of developing an application software named pyBIMstab that is capable of randomly generating bimsoil/bimrock structures inside a slope; defining automatically the surfaces that pass around the blocks by applying a pathfinding algorithm named A*; and evaluating the factor of safety of those tortuous surfaces with limit equilibrium methods. The application software pyBIMstab was used to perform thousands of analysis for different conditions and conclusion were obtained from that work. Finally, a methodology is proposed to properly perform analysis in slopes made of bimsoils/bimrocks in a stochastic way to deal with the uncertainties related to the wide range of factors of safety that can occur even with bimsoils/bimrocks having the same block proportions.